Priorities for synthesis research in ecology and environmental science. Issue 1 (11th January 2023) - Halpern, Benjamin S.; Boettiger, Carl; Dietze, Michael C.; Gephart, Jessica A.; Gonzalez, Patrick; Grimm, Nancy B.; Groffman, Peter M.; Gurevitch, Jessica; Hobbie, Sarah E.; Komatsu, Kimberly J.; Kroeker, Kristy J.; Lahr, Heather J.; et al.
Abstract: Synthesis research in ecology and environmental science improves understanding, advances theory, identifies research priorities, and supports management strategies by linking data, ideas, and tools. Accelerating environmental challenges increases the need to focus synthesis science on the most pressing questions. To leverage input from the broader research community, we convened a virtual workshop with participants from many countries and disciplines to examine how and where synthesis can address key questions and themes in ecology and environmental science in the coming decade. Seven priority research topics emerged: (1) diversity, equity, inclusion, and justice (DEIJ), (2) human and natural systems, (3) actionable and use‐inspired science, (4) scale, (5) generality, (6) complexity and resilience, and (7) predictability. Additionally, two issues regarding the general practice of synthesis emerged: the need for increased participant diversity and inclusive research practices; and increased and improved data flow, access, and skill‐building. These topics and practices provide a strategic vision for future synthesis in ecology and environmental science.